2022
DOI: 10.1002/er.7753
|View full text |Cite
|
Sign up to set email alerts
|

Improved salp swarm algorithm based on particle swarm optimization for maximum power point tracking of optimal photovoltaic systems

Abstract: In this study, an improved salp swarm algorithm based on particle swarm optimization for maximum power point tracking of optimal photovoltaic systems is investigated. The effect of PV partial shading conditions, uniform and fasttracking irradiance, duty cycle, frequency, temperature changes, and load types, and besides some comparative studies of different algorithms are adequately examined for better performance study of the proposed technique. The proposed improved salp swarm algorithm based particle swarm o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 49 publications
(73 reference statements)
0
19
0
Order By: Relevance
“…In order to obtain the optimal dynamic model, an improved quantum particle swarm optimization algorithm [9,10] is used to optimize the delay parameters of the dynamic model. The number of particle dimensions is optimized to be 7.…”
Section: Modeling Resultsmentioning
confidence: 99%
“…In order to obtain the optimal dynamic model, an improved quantum particle swarm optimization algorithm [9,10] is used to optimize the delay parameters of the dynamic model. The number of particle dimensions is optimized to be 7.…”
Section: Modeling Resultsmentioning
confidence: 99%
“…The overall simulation was illustrated at 25 ms, and the results were observed and indicated that the proposed technique curves paired well with that of the preceding literature 32 under weather‐ varying conditions. However sudden decrease and increase occurred at 45 and 50 ms, respectively, it has accurately tracked the global maximum power at 72 ms for two power values of 80 and 60 W, whereas the conventional method failed to track the global maximum power (GMP) 33‐35 from the origin zero with enormous decay until 138 and 116 ms for different powers of 80 and 60 W, respectively and has presented rough oscillations.…”
Section: The Proposed Trt‐bbc Working Principlementioning
confidence: 95%
“…[16] proposed a novel hybrid series salp particle Swarm optimization (SSPSO) which is highly required for suburb area applications where the partial shading conditions are frequent. [17] has explored an improved salp swarm algorithm based on particle swarm optimization for maximum power point tracking of optimal photovoltaic systems. [7] The PSO traditional technique was supposed to be the most efficient method of tracking the maximum power in the pattern shading situations.…”
Section: Literature Reviewmentioning
confidence: 99%